2013
DOI: 10.1155/2013/879501
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism Study of Competitive Inhibition of Jack‐Bean Urease by Baicalin

Abstract: Baicalin (BA) is the principal component of Radix Scutellariae responsible for its pharmacological activity. In this study, kinetics and mechanism of inhibition by BA against jack-bean urease were investigated for its therapeutic potential. It was revealed that the IC50 of BA against jack-bean urease was 2.74 ± 0.51 mM, which was proved to be a competitive and concentration-dependent inhibition with slow-binding progress curves. The rapid formation of initial BA-urease complex with an inhibition constant of K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Therefore, SH‐blocking reagent was employed to examine its effects on the inhibitory activity of PA against ureases. When DTT was added to the pre‐incubation medium, instead restoring the inhibition of urease activity by some reported compounds like allicin, quinine, and flavonoid (Juszkiewicz et al ., ; Kot, ; Tan et al ., ), the inhibitory activity of PA was strengthened by DTT. Chemical studies have shown that various sesquiterpenes react with thiols (Kupchan et al ., ; Kupchan et al ., ).…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, SH‐blocking reagent was employed to examine its effects on the inhibitory activity of PA against ureases. When DTT was added to the pre‐incubation medium, instead restoring the inhibition of urease activity by some reported compounds like allicin, quinine, and flavonoid (Juszkiewicz et al ., ; Kot, ; Tan et al ., ), the inhibitory activity of PA was strengthened by DTT. Chemical studies have shown that various sesquiterpenes react with thiols (Kupchan et al ., ; Kupchan et al ., ).…”
Section: Discussionmentioning
confidence: 93%
“…Besides methyl gallate and related derivatives, 37 other plant phenolic compounds, such as (iso) quercitrin, avicularin, guaijaverin, flavonoid glucosides and shoreaphenol, were also reported to inhibit jack bean urease. 29,30,38,39 Interestingly, structural modifications on PA, VN and SA dramatically improved their ability to inhibit the ureolytic activity of jack bean urease (Figure 2). Indeed, the conversion of phenolic aldehydes to derivatives bearing urea or thiourea core (Figure 1) yielded the VN derivative The compounds 2A7 and 2B10 (PA derivatives), 2A9 (SA derivative) and 2D2 (VN derivative) were employed at different concentrations (0.3 to 1.6 mM) in reactions containing urea ranging from 1 to 32 mmol L -1 and 12.5 mU urease.…”
Section: Discussionmentioning
confidence: 99%
“…PA is used for the quality control objective of patchouli oil in pharmaceutical industry (The Pharmacopoeia Commission of PRC 2010). Accumulating reports have demonstrated that PA had multiple effects such as anti-inflammatory [7, 8], antivirus [912], antimicrobial [13–17], and insecticidal [18, 19], protective effect on fluidity of intestinal epithelial cells [20], protective effect on acute lung injury [21], radical-scavenging activity [22], inhibitory activity on platelet-activating factor (PAF) activation [23], and antiemetic activity [24]. …”
Section: Introductionmentioning
confidence: 99%